2021
DOI: 10.5014/ajot.2021.75s2-rp328
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Self-Paced Online Learning and Hands-On Lab on OT Student Knowledge

Abstract: Date Presented Accepted for AOTA INSPIRE 2021 but unable to be presented due to online event limitations. The health and safety of OT clientele demand students' proficiency in a multitude of evaluation and intervention approaches. Subsequently, educators must use evidence-based instructional approaches to facilitate efficient high-quality learning. In this research presentation, we discuss a randomized controlled educational intervention designed to train entry-level OT students how to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…20,46 A randomized controlled study showed that online learning followed by hands-on lab practice resulted in the best learning outcome compared to only online or only handson lab for occupational therapy students learning how to evaluate community accessibility. 48 In addition, the social learning theory suggests that peer assessment in which a student assesses another student is beneficial for both the student assessor and the student being assessed as socialization and communication between students facilitate deeper learning. 47 The impact is that this work serves as a model for developing efficient yet effective training that fits into therapists' work schedule and prepares them to apply novel rehabilitation devices to increase therapists' device adoption in practice.…”
Section: Discussionmentioning
confidence: 99%
“…20,46 A randomized controlled study showed that online learning followed by hands-on lab practice resulted in the best learning outcome compared to only online or only handson lab for occupational therapy students learning how to evaluate community accessibility. 48 In addition, the social learning theory suggests that peer assessment in which a student assesses another student is beneficial for both the student assessor and the student being assessed as socialization and communication between students facilitate deeper learning. 47 The impact is that this work serves as a model for developing efficient yet effective training that fits into therapists' work schedule and prepares them to apply novel rehabilitation devices to increase therapists' device adoption in practice.…”
Section: Discussionmentioning
confidence: 99%